Coals’ proneness to airborne respirable dust formation - Svetlana A. Epshtein; Elena L. Kossovich; Nadezhda N. Dobryakova; Jie Hao; Yulia E. Andreeva; Vera A. Krasilova (International Journal of Coal Science & Technology, 2025)
Abstract The paper contains the results of investigation of interconnections between coals’ vitrinite structural features, mode of its crushing under the cyclic nanoindentation with increasing peak load and coals’ proneness to formation of airborne respirable dust (ARD) with particles sized < 10 μm (PM10). A specific value of PM10 contents in coals normalized on a fines fraction (with particles sizes of less than 200 μm) was used as a measure of proneness to ARD formation. It has been shown that the aforementioned parameter is predefined by the ratio of amorphous and crystalline carbon compounds in vitrinite and the mode of its crushing. Some preliminary investigation have been done in order to characterize the involvement of inertinite in ARD formation. It was proposed that the inertinite is not as actively involved in the processes of ARD formation of coals as vitrinite, having a more diverse structural features in terms of amorphous to crystalline carbon compounds ratio.